(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: Almost all hemophilia patients are treated with fresh frozen plasma and other alternatives regardless of anemic status, so it is important to identify the patients who are chronically anemic and thereby those cases to be treated accordingly. As no previous work and research regarding study of anemia among hemophilia patients were done in our country and abroad as far as I know, so data regarding this study from online source could not be compiled here. Objective: The objective of the study was to evaluate the degree of anemic status among hemophilia patients who were receiving FFP for long time. Materials and Method: It was a prospective type of observational study. The study was carried out in the Department of Transfusion Medicine, BSMMU, Dhaka, Bangladesh. This study was conducted from July 2011 to June 2012 for a period of one (1) year. 60 patients with hemophilia were selected from patients attending at day care unit of Transfusion Medicine dept. of BSMMU. Results: Among 60 patients, according to degree of anemia majority cases are moderately anemic which were 35(58.33%) cases followed by mildly anemic which were 15(25.00%) cases, Severely anemic were 2(3.33%).Non anemic cases were 10(16.67%). Bangladesh Journal of Medical Science Vol.17(4) 2018 p.573-575